Moving from multi-channel to Omni-channel retailing: Special issue introduction. (March 2022) - Thaichon, Park; Phau, Ian; Weaven, Scott
Abstract: In this special issue "Moving from Multi-Channel to Omni-Channel Retailing", the Journal of Retailing and Consumer Services presents a series of papers covering topics to gain a better understanding of research and practices in the move toward Omni-channel retailing. The aim of the special issue is to gain a better understanding of marketing theory and practice in multi-channel and Omni-channel retailing. The topics for the special issue include, but are not limited to (1) The impact of channel integration on consumers' channel preferences; (2) Service integration in Omni-channel retailing; (3) Customer touchpoint in the context of Omni-channel retailing; (4) Consumer behaviour in Omni-channel retailing; and (5) Building and maintaining customer relationships via Omni-channel retailing.